Computational tomography and CFD simulation of a biofilter treating a toluene, formaldehyde and benzo[α]pyrene vapor mixture. (February 2020) - Moreno-Casas, Patricio A.; Scott, Felipe; Delpiano, José; Vergara-Fernández, Alberto
Abstract: In this work, a 3D computational tomography (CT) of the packing material of a laboratory column biofilter is used to model airflow containing three contaminants. The degradation equations for toluene, formaldehyde and benzo[α]pyrene (BaP), were one-way coupled to the CFD model. Physical validation of the model was attained by comparing pressure drops with experimental measurement, while experimental elimination capacities for the pollutants were used to validate the biodegradation kinetics. The validated model was used to assess the existence of channeling and to predict the impact of the three-dimensional porous geometry on the mass transfer of the contaminants in the gas phase. Our results indicate that a physically meaningful simulation can be obtained using the techniques and approach presented in this work, without the need of performing experiments to obtain macroscopic parameters such as gas-phase axial and radial dispersion coefficients and porosities. Graphical abstract: Image 1 Highlights: Realistic 3D description of the porous bed using computational tomography (CT). Full 3D velocity field (CFD) of air flow through a laboratory column biofilter. Fully 3D degradation representation for toluene, formaldehyde and BaP. Graphical description and quantification of preferential flow. Comparison of the 3D CFD-CT model with a 1D plug-flow model.